Broken beer bottle as a cause of sigmoid perforation: A summary of causes and predictors in the management of traumatic and non-traumatic colorectal perforation. (August 2021) - Ospina-Pérez, Christian German; Álvarez-Acuña, Ana Milena; López-Álvarez, Lina María; Ospina-Pérez, Rosa María; Lozada-Martínez, Ivan David; Rahman, Sabrina
Abstract: Introduction and importance: The presence of foreign bodies at the colorectal level and associated complications is a problem that has become increasingly common in emergency departments. This condition carries high health costs, in addition to having high morbidity and mortality rates, due to the large number of complications such as perforation. Case presentation: 46-year-old male patient, who came to the emergency department of a low-level hospital with a clinical picture of approximately one day of evolution consisting of the violent introduction of a foreign body (bottle) at the anorectal level secondary to aggression in a fight, with subsequent endoluminal rupture. Clinical discussion: The most recent evidence indicates that the incidence of perforation as a complication of colorectal foreign body introduction is low. However, the presence of profuse bleeding, advanced age, presence of comorbidities and sepsis are predictors of poor prognosis in these cases. In general, perforation secondary to non-traumatic causes is more frequent, being predominantly due to colorectal cancer, ischemia, diverticulitis, inflammatory bowel disease, inadequate use of enema, iatrogenic endoscopy or anorectal manometry or fecal impaction. The presence of unfavorable factors prolongs hospital stay, the risk of reoperation, perianal infection, peritonitis, sepsis and wound infection, generating mortality rates of up to 38%. Conclusion: Colorectal perforation is more frequent in non-traumatic situations and carries health costs and risk of mortality. Its management depends on hospital aspects, clinical context of the patient and training of health personnel. However, most of the outcomes are favorable. Highlights: The incidence of perforation as a complication of colorectal foreign body introduction is low. Colorectal perforation is more frequent in non-traumatic situations. The presence of unfavorable factors increases risk of morbidity and mortality.